A scientific study of late Islamic blue‐white stonepaste wares of Iran. (13th March 2022) - Ma, Yanying; Li, Zhimin; Zhang, Liangren; Wu, Jingwei; Xiong, Yingfei; Vahdati, Ali; Zhang, Jiayang
Abstract: Blue‐white stonepaste wares were an outgrowth of the bursting innovations of Near Eastern potters striving to imitate Chinese products during the Islamic period. Building on the results of previous research, this paper seeks to increase our knowledge of this type of ceramics by analyzing 16 Qajar period samples from Tepe Naderi in North Khorasan Province, Iran, with stereo microscopy, Raman spectroscopy and scanning electron microscopy. It appears that the bodies of these samples are characterized by high silicon and high alkali, a hallmark of the traditional Iranian stonepaste. They are coated with transparent alkali glazes and colored with the chromogenic elements of Cr, Co, Fe and Mn derived from chromite, hematite and cobalt ferrite, the latter of which is the decomposed phase of cobaltite ore known from Qamsar in Iran. The provenance of these samples cannot be probed at present, however, due to the lack of study of contemporaneous ceramics in the Near East.